A study of manpower planning in relation to the needs of primary and secondary education in Thailand - Duangporn Beokhaimook 1942- ([Quezon City s.n.], 1969)
This study examined the existing policies and programme of teacher preparation in Thailand. The study determined whether the number of teachers produced meet the future demand of the increasing school population, in order to explore the needs for manpower in Thailand and to determine the extent by which the current programme of teacher preparation is related to the manpower development planning of Thailand.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Teachers, Training of -- Thailand; Education -- Thailand; Manpower -- Thailand